2012
DOI: 10.1097/ede.0b013e31823b6139
|View full text |Cite
|
Sign up to set email alerts
|

Radon and Skin Cancer in Southwest England

Abstract: This ecologic study suggests that environmental radon exposure may be a risk factor for squamous cell carcinoma. Further study is warranted to overcome ecologic design limitations and to determine whether this relationship is generalizable to national and international settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Published studies have found an association between residential radon and leukaemia, central nervous system [11], skin cancer [12] and oesophageal cancer [13]. We could not find any study assessing exclusively the possible relationship between oral and pharyngeal cancer and radon, but it is possible to extract data from larger studies where many cancer types have been analysed.…”
Section: Introductionmentioning
confidence: 89%
“…Published studies have found an association between residential radon and leukaemia, central nervous system [11], skin cancer [12] and oesophageal cancer [13]. We could not find any study assessing exclusively the possible relationship between oral and pharyngeal cancer and radon, but it is possible to extract data from larger studies where many cancer types have been analysed.…”
Section: Introductionmentioning
confidence: 89%
“…Importantly, all metastases and deaths from SCC occurred among patients who received voriconazole [ 162 ]. Another study among lung transplant recipients found a threefold increased risk of SCC and a 5.6 % increase in risk of SCC with each 60-day voriconazole exposure at a standard dose [ 163 ]. The risk of aggressive SCC has led many lung transplant centers to avoid voriconazole and rely on alternatives [ 164 ].…”
Section: Other Risk Factorsmentioning
confidence: 94%
“…There have also been reports associating radon with a variety of other cancers: Brain (Bräuner et al, 2013); Gastro-Intestinal Tract (Kjellberg and S., 1995); Central Nervous System (Del Risco Kollerud et al, 2014); Oesophagus (Ruano-Ravina et al, 2014); Prostate (Eatough and Henshaw, 1990) and Skin (Wheeler et al, 2012). Further investigations are required to confirm or otherwise these associations before any firm conclusions can be drawn.…”
Section: Introductionmentioning
confidence: 99%